PLC-Mediated Signaling Pathway in Pollen Tubes Regulates the Gametophytic Self-incompatibility of Pyrus Species - Qu, Haiyong; Guan, Yaqin; Wang, Yongzhang; Zhang, Shaolin (Frontiers in Plant Science, 2017)
Among Rosaceae species, gametophytic self-incompatibility (GSI) is controlled by a single multi-allelic S locus, which is composed of the pistil-S and pollen-S genes. The pistil-S gene encodes a polymorphic ribonuclease (S-RNase), which is essential for identifying self-pollen. However, the S-RNase system has not been fully characterised. In this study, self-S-RNase inhibited Ca2+-permeable channel activity at pollen tube apices and selectively decreased phospholipase C (PLC) activity in the plasma membrane of Pyrus pyrifolia pollen tubes. Self-S-RNase decreased the Ca2+ influx through a PLC-mediated signalling pathway. Phosphatidylinositol-specific PLC has a 26-amino acid insertion in pollen tubes of the ‘Jinzhuili’ cultivar, which is a spontaneous self-compatible mutant of the ‘Yali’ cultivar. ‘Yali’ plants exhibit a typical S-RNase-based GSI. Upon self-pollination, PLC gene expression is significantly higher in ‘Jinzhuili’ pollen tubes than that in ‘Yali’ pollen tubes. Moreover, the PLC in pollen tubes can only interact with one of the two S-RNase from the style. In the Pyrus bretschneideri Rehd, the PLC directly interacted with the S7-RNase in the pollen tube, but not with the S34-RNase. Collectively, our results reveal that the effects of S-RNase on PLC activity are required for S-specific pollen rejection and PLC-IP3 participate in self-incompatibility reaction of Pyrus species.